FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN BAYI BERAT LAHIR RENDAH (BBLR) DI RUMAH SAKIT BUNDA PALEMBANG TAHUN 2023 - Kurnianti, Nia; Rizki Amalia; Eka Afrika; Rini Gustina (JURNAL KESEHATAN INDRA HUSADA, 2025)
One of the causes of the increasing maternal mortality rate is hypertension in pregnant women. Cases of hypertension are currently very high increase in the world, in Indonesia, in South Sumatra and in Banyuasin Regency. The purpose of this study was to determine the relationship between age, sleep quality, and obesity with the incidence of gestational hypertension in pregnant women at TPMB Ria Permata Sari, Banyuasin Regency in 2024. The type and design of the study were wer quantitative using an analytical survey method with a cross-sectional approach. The number of samples in this study was 30 respondents using the total sampling technique The results of the chi-square statistical test for the sleep quality variable obtained a p value= 0.461 (> 0.05) which means there was no relationship between sleep quality and gestational hypertension. The obesity variable obtained a p value = 0.000 (<005) which means there was a relationship between obesity and gestational hypertension The age variable obtained a p value 0.042 (<0.05) which means that there was a relationship between age and gestational hypertension in pregnant women at TPMB Ria Permata Sari, Banyuasin Regency in 2024. It is concluded that there is a relationship between age and obesity, and there is no relationship between sleep quality and hypertension simultaneously or partially with the incidence of gestational hypertension at TPMB Ria Permata Sari, Banyuasin Regency in 2024 In this study, it is hoped that health workers can provide better services and supervision of hypertension problems in pregnant women.